Highly Active Antiretroviral Therapy (HAART)-Related Hypertriglyceridemia Is Associated With Failure of Recovery of CD14lowCD16+ Monocyte Subsets in AIDS Patients. Issue 27 (July 2015) - Han, Junyan; Zhao, Hongxin; Ma, Yaluan; Zhou, Haiwei; Hao, Yu; Li, Yanmei; Song, Chuan; Han, Ning; Liu, Xiangyi; Zeng, Hui; Qin, Mingzhao; Vallejo., Alejandro
<x xml:space="preserve">Abstract</x> Abstract As cellular reservoirs, CD16+ monocyte subsets play important roles in the progression of HIV infection. Previous studies have shown that highly active antiretroviral therapy (HAART) reduced the percentages of CD14highCD16+ monocyte subsets, but did not recover the percentages of CD14lowCD16+ subsets. Eighty-four chronic HIV-infected, HAART-naïve individuals and 55 HIV-negative subjects (31 without hyperlipidemia and 24 with hypertriglyceridemia) were enrolled. Plasma HIV-1 RNA levels, CD4+ T-cell counts, triglycerides, total cholesterol, high-density lipoprotein, and low-density lipoprotein were followed up for 48 weeks during HAART treatment in the longitudinal study. We found that mild hypertriglyceridemia in HIV-negative subjects and HIV-infected patients, naïve to HAART, did not affect the percentage of monocyte subsets. However, a failure of CD14lowCD16+ subset recovery was observed in patients with HAART-related hypertriglyceridemia at 48 weeks. Thus, HAART-related hypertriglyceridemia altered homeostasis of monocyte subsets to antiviral therapy, which might further affect immune reconstitution.